Impact of Blood Flow Restriction Resistance Training on Mobility, Balance, and Stability in Middle-Aged Adults - AbuEid, Samer (Journal of Physical Education, 2025)
This study investigates the effectiveness of Blood Flow Restriction (BFR) resistance training in enhancing mobility, balance, and stability in middle-aged adults, key factors for maintaining independence and reducing fall risk. A total of 48 participants (mean age 55.72 ± 1.85 years; mean height 1.74 ± 0.06 m; mean weight 73.47 ± 8.18 kg) were randomly assigned to either a BFR training group or a control group. The BFR group completed a 12-week low-intensity resistance training program, while the control group followed a traditional exercise routine. Functional Movement Screen (FMS) tests assessed mobility, balance, and stability before and after the intervention. Results revealed significant improvements in the BFR group for balance (mean increase: +1.33, p < 0.001), stability (+1.08, p < 0.001), and lower body mobility, particularly in the Active Straight Leg Raise (ASLR) test (+0.38, p < 0.05). Minimal changes were observed in the control group. These improvements align with enhanced neuromuscular activation, proprioception, and core strength induced by the hypoxic environment of BFR training. The findings highlight BFR training as a practical, low-intensity intervention for addressing age-related functional declines. It offers an accessible alternative for individuals unable to perform high-intensity resistance training, with potential applications in fall prevention, rehabilitation, and functional health optimization. Future research should examine its long-term effects and broader applicability across diverse populations.